2017
DOI: 10.1590/s1980-220x2016018903211
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, stress and depression in family members of patients with heart failure

Abstract: Objective: Identifying the level of anxiety, stress and depression symptoms in family members of patients with heart failure; identifying the relationship between these feelings with sociodemographic and clinical variables. Method: A cross-sectional study carried out with 100 family members. Depression, anxiety, and stress were evaluated by the Beck Depression and Anxiety Inventories and the Perceived Stress Scale -10. The relationship between feelings and variables was performed through the t-test, Mann-Whitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
4
1
2
Order By: Relevance
“…This result was consistent with the results of the study by Famis et al (22) who showed that anxiety of the relatives varied from 35% to 45%. Lacerda et al (23) found anxiety in 77% of patients' relatives but Bolosi et al (4) found anxiety in 13.9% of patients, which was lower than the rate of anxiety in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…This result was consistent with the results of the study by Famis et al (22) who showed that anxiety of the relatives varied from 35% to 45%. Lacerda et al (23) found anxiety in 77% of patients' relatives but Bolosi et al (4) found anxiety in 13.9% of patients, which was lower than the rate of anxiety in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…for interventions, should guide the patient in relation to the pathology, such as complications, limitations and basic daily care with health, adherence to treatment, and explaining the harmful effects of non-adherence. When the patient knows all the stages of his pathology, he tends to influence treatment adherence and the implementation of preventive measures in order to minimize more serious complications [14].…”
Section: Resultsmentioning
confidence: 99%
“…As we also aimed to explore which factors affect the occurrence of depressive and anxiety symptoms, in our interviews, we collected the following information: "chronic pain", [13][14][15] "sup-port from the family" 16,17 and "burden of medical expenses on the family", 18 which have been found to be related to depression and anxiety in previous studies. In addition, given that the diagnosis of malignant tumors is often concealed from elderly individuals in China, we also added the question "how much do you know about your disease?"…”
Section: Methodsmentioning
confidence: 99%